Cara Merawat Penderita Stunting dengan Pola Hidup Sehat, Pemenuhan Gizi Anak dan Ibu Hamil di Desa Kumbang Kecamatan Blangmangat Kota Lhokseumawe - Siska Desta Roza; Novianti (CV. CENDIKIA JENIUS INDONESIA, 2023)
In Indonesia, stunting is still a health problem. This condition is caused by malnutrition from pregnancy until the child is 2 years old. specifically, such as Kumbang Village, Blang Mangat District, Lhokseumawe City. The problem of stunting is still found in a relatively large number of cases. Based on the results of interviews with community leaders, stunting conditions are still often experienced by the people of Kumbang Village, Blang Mangat District, Lhokseumawe City. The aim of this activity is to increase awareness of mothers under five whose children are stunting and pregnant women about how to care for stunting sufferers with a healthy lifestyle, fulfilling nutritional requirements for children and pregnant women. The methods used in this activity are lectures, questions and answers and discussions to increase understanding about stunting. Implementation of activities in October 2023 in Kumbang Village, Blang Mangat District, Lhokseumawe City. Results of the pre-test mean score and post-test mean score before and after conducting counseling. It was found that the participants' average pre-test score was 6.21 and the participants' post-test average score was 8.42 (p=0.000). The conclusion was that there was an increase in the participants' knowledge before the counseling was carried out compared to after the counseling was carried out. It is hoped that through this activity, family members can participate in reducing stunting rates in Kumbang Village, Blang Mangat District, Lhokseumawe City.